1995
DOI: 10.1016/1074-7613(95)90060-8
|View full text |Cite
|
Sign up to set email alerts
|

PU.1 is not essential for early myeloid gene expression but is required for terminal myeloid differentiation

Abstract: We have previously shown using gene targeting that PU.1 is essential for the development of lymphoid and myeloid lineages during fetal liver hematopoiesis. We now show that PU.1 is required for the maturation of yolk sac-derived myeloid progenitors and for the differentiation of ES cells into macrophages. The role of PU.1 in regulating target genes, thought to be critical in the development of monocytes and granulocytes, has been analyzed. Early genes such as GM-CSFR, G-CSFR, and myeloperoxidase are expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
124
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 184 publications
(135 citation statements)
references
References 43 publications
9
124
2
Order By: Relevance
“…Similar results were obtained for day 8.5 and 10.5 yolk sacs, which represent earlier sites of hematopoiesis [17]. This indicates that a similar block in myeloid differentiation occurs during yolk sac hematopoiesis.…”
Section: Pu1 In Hematopoiesissupporting
confidence: 75%
See 3 more Smart Citations
“…Similar results were obtained for day 8.5 and 10.5 yolk sacs, which represent earlier sites of hematopoiesis [17]. This indicates that a similar block in myeloid differentiation occurs during yolk sac hematopoiesis.…”
Section: Pu1 In Hematopoiesissupporting
confidence: 75%
“…[17,18]. The failure of PU.1 -/-ES cells to differentiate into macrophages can be rescued by a PU.1 transgene under the control of its own promoter [17]. This result confirms the pivotal role that PU.1 serves in controlling macrophage differentiation.…”
Section: Exploring Pu1 Function In An Es Cell In Vitro Differentiatisupporting
confidence: 72%
See 2 more Smart Citations
“…PU.1 null progenitor cells are not responsive to GM-CSF, G-CSF, or M-CSF. Transduction of PU.1 null progenitor cells with the M-CSFR overcomes the block in M-CSF-induced cell proliferation but does not restore full myeloid cell differentiation to these progenitor cells (Olson et al, 1995;DeKoter et al, 1998). Further studies concluded that PU.1 controls cellular differentiation by regulating distinct proliferation and differentiation pathways.…”
Section: Stem/progenitor Cell Differentiation: Stochastic or Inductivementioning
confidence: 98%